Preliminary in Vitro Screening of Antibacterial Activity of Leaf Extract from Ficus natalensis subsp. natalensis Hochst. (Moraceae) Against Fish Pathogens - Tkachenko, Halyna; Buyun, Lyudmyla; Kasiyan, Olha; Terech-Majewska, Elzbieta; Honcharenko, Vitaliy; Prokopiv, Andriy; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The aim of this study was to screen the antibacterial efficacy of ethanolic extract obtained from the leaves of Ficus natalensis subsp. natalensis Hochst. against fish pathogens, Aeromonas hydrophila, Citrobacter freundii, Pseudomonas fluorescens, Yersinia ruckeri and to evaluate the possible use of this plant in preventing infections caused by these bacteria in aquaculture. The bacterial growth inhibition tests were carried out using agar well diffusion method with the use of crude ethanolic extract. Muller-Hinton agar plates were inoculated with 200 and 400 µL of standardized inoculum (108 CFU/mL) of the bacterium. In our study, the A. hydrophila strain (200 and 400 µl of standardized inoculum) revealed intermediate susceptibility to an ethanolic extract (inhibition zone diameters ranged from 10.0 to 11.8 mm). C. freundii (200 and 400 µl) was resistant to ethanolic extract (7.5 and 11.7 mm). The extract exhibited intermediate antibacterial activity against P. fluorescens causing a zone of inhibition, comprising at least 10.2–12.8 mm for 200 µL and 7.4–11.2 mm for 400 µL of bacterium strain. Y. ruckeri (200 and 400 µl) revealed intermediate susceptibility (8.0 and 16.5 mm). This may be because the herbs have more than one extractable active compound that provides antimicrobial activity. Further chemical analysis of the aforementioned plant extract should be performed to determinate chemical composition and identify the exact phytocompounds responsible for the antimicrobial activity.